Identification of Anaplasma marginale adhesins for bovine erythrocytes using phage display - Noh, Susan M.; Ujczo, Jessica; Alperin, Debra C. (Frontiers in Tropical Diseases, 2024)
Bovine anaplasmosis, caused by Anaplasma marginale, is one of the most common tick-borne diseases of cattle and has a worldwide distribution. The high costs of bovine anaplasmosis are due to treatment, decreased production, and outbreaks resulting in high mortality. The impact of bovine anaplasmosis is greatest in tropical and subtropical regions where tick vectors are abundant year around. Prevention generally relies on the use of tetracyclines to prevent disease and acaricides to reduce tick burdens. Thus, additional methods to prevent disease while reducing the use of antibiotics are needed. Protection can be reliably achieved with immunization using outer membrane proteins, thus allowing for the possibility for development of a recombinant vaccine. However, prioritizing the selection and testing of antigens from the protective outer membrane extract remains a challenge. Because A. marginale is an obligate intracellular pathogen, surface proteins that mediate adhesion to host cells, primarily red blood cells (RBCs), are functionally relevant vaccine candidates. With some exceptions, the proteins that bind RBCs remain unknown. To address this gap, a phage display library expressing 66 A. marginale proteins was screened to identify adhesins for bovine RBCs. Of the screened proteins, 73% were eliminated due to poor binding to RBCs. Several potential adhesins were identified, including Msp1b and OmpA, which are known adhesions for bovine RBCs and tick cells, respectively. Additionally, Mlp3, Am779, Msp3, and Omp13 met the criteria as RBCs adhesins and may serve as high priority vaccine candidates for future testing.